IgA class antibodies and flow cytometric cross-matching in renal transplantation - Doran, Trevor; Süsal, Caner; Opelz, Gerhard; Geczy, Andrew F. (Transplantation, 1999)
BACKGROUND: The established method of pretransplant cross-matching does not detect IgA antibodies, and IgA antibodies have thus been ignored when assessing patients for transplantation. The aim of this study was to detect IgA allo- and autoreactive antibodies using flow cytometry and to correlate the results with transplant outcome. METHODS: Pretransplant sera from 231 sequential renal recipients were tested for serum IgA levels and antibodies directed against the Fab portion of the human IgG molecule. Fifty-nine recipients with sufficient stored donor lymphocytes were also tested by flow cytometry for donor-specific alloantibodies of the IgA isotype. RESULTS: Graft survival was improved in recipients with higher IgA levels. High IgA anti-Fab levels led to a significantly higher 1-year graft survival (P<0.05). Graft survival was further enhanced where both serum IgA and IgA anti-Fab were raised (P<0.01). Although the mean IgA level tended to be higher for recipients with a positive IgA flow cytometric cross-match (FCXM), the IgA FCXM was not associated with increased IgA anti-Fab, suggesting that the IgA FCXM is detecting a different subset of IgA reactivity. Additionally, for primary grafts, a positive IgA FCXM was not associated with enhanced graft survival. CONCLUSIONS: Within the repertoire of IgA activity, there are two recognizable groups, the IgA anti-Fab specificity, which is significantly associated with enhanced graft survival, and that detected by the IgA FCXM, which surprisingly is more likely to be positive in less sensitized first grafts and is not associated with enhanced graft survival.
Gesehen am 19.02.2021